2013
DOI: 10.1177/0194599813497923
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Reconstruction after Intra‐arterial Chemotherapy with Concomitant Radiation

Abstract: Microvascular reconstruction following HYPERRADPLAT appears to result in a high number of arterial related complications. This experience implies an important delayed treatment effect of HYPERRADPLAT occurs upon recipient arteries. The manner in which this effect may occur in recipient arteries in the setting of more conventional chemoradiation requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Changes including intimal thickening, proteoglycan deposition, and inflammatory cell infiltrate that are consistent with early stages of atherosclerosis were observed in the tissue samples obtained from recipient arteries within a few years after irradiation. In another study, arterial thrombosis and flap failure complications were reported at rates of 50% and 25%, respectively, in microvascular reconstructions after chemoradiation therapy (21).…”
Section: Discussionmentioning
confidence: 92%
“…Changes including intimal thickening, proteoglycan deposition, and inflammatory cell infiltrate that are consistent with early stages of atherosclerosis were observed in the tissue samples obtained from recipient arteries within a few years after irradiation. In another study, arterial thrombosis and flap failure complications were reported at rates of 50% and 25%, respectively, in microvascular reconstructions after chemoradiation therapy (21).…”
Section: Discussionmentioning
confidence: 92%
“…External beam radiation has been shown to cause changes to the tunica intima of arteries. 26,27 However, although some small case series showed increased arterial related complications, 28 others larger series have not. 11,27 Even with extensive prior treatment and neck procedures, we found in our series of patients that the facial artery, lingual artery, and superior thyroid artery often remain viable donor options.…”
Section: Discussionmentioning
confidence: 99%
“…In this way a perfect like-with-like tissue restoration is reached, leading to a good and stable result. For example, this procedure can be particularly useful after radiotherapy or high-energy traumas, which critically impair the quality of the vessels and lead to a much higher rate of complication (Valentino et al, 2013).…”
Section: Casementioning
confidence: 99%